Modeling geomagnetic induction in submarine cables - Chakraborty, Shibaji; Boteler, David H.; Shi, Xueling; Murphy, Benjamin S.; Hartinger, Michael D.; Wang, Xuan; Lucas, Greg; Baker, Joseph B. H. (Frontiers in Physics, 2022)
Submarine cables have become a vital component of our modern infrastructure, but past submarine cable natural hazard studies have mostly focused on potential cable damage from landslides and tsunamis. There are only a handful of studies that examine the possibility of space weather effects in submarine cables. The main purpose of this study is to develop a computational model, based on Python, of geomagnetic induction on submarine cables. The model is used to estimate the induced voltage in the submarine cables in response to geomagnetic disturbances. It also takes into account newly acquired knowledge from magnetotelluric studies and associated investigations of Geomagnetically Induced Currents in power systems. We describe the Python-based software, its working principle, inputs/outputs based on synthetic geomagnetic field data, and compare its operational capabilities against analytical solutions. We present the results for different model inputs, and find: (i) the seawater layer acts as a shield in the induction process: the greater the ocean depth, the smaller the seafloor geoelectric field; (ii) the model is sensitive to the ocean-earth layered conductivity structure.